Uptight and in your face : coping with an anxious boss, parent, spouse, or lover - Brown, Nina W. (Praeger, 2011)
It is often stated that communication is the most important aspect of creating an effective relationship or achieving goals when working with another individual or within a team. But how does one communicate with someone who is too intense, anxious, or self-absorbed to hear anything you're trying to say? In Uptight and In Your Face: Coping with an Anxious Boss, Parent, Spouse, or Lover the author presents an invaluable tutorial to successfully interact with the most frustrating and taxing people in your life. This text examines the five most common types of uptight people to illustrate how the underlying patterns of intensity, anxiety, and self-absorption are displayed. Considerable attention is given to help readers understand how they may be contributing to their own distress. The final chapters present numerous coping and self-development strategies that will help reduce or eliminate many of the detrimental effects of interacting with high-stress people. Descriptions of complex psychological concepts are explained in everyday language.